Circulating serum miRNAs as potential biomarkers for nephroblastoma. Issue 8 (18th March 2015) - Ludwig, Nicole; Nourkami‐Tutdibi, Nasenien; Backes, Christina; Lenhof, Hans‐Peter; Graf, Norbert; Keller, Andreas; Meese, Eckart
Abstract Background Nephroblastoma (or Wilms tumor—WT) is the most common childhood kidney cancer. In Europe, nephroblastoma is treated with preoperative chemotherapy without histological confirmation by biopsy. Therefore, minimal‐invasive diagnostic markers confirming nephroblastoma diagnosis are highly warranted. Procedure In our study, we aim to identify circulating miRNAs with diagnostic potential for differentiating nephroblastoma from controls. We determined the level of 19 miRNAs in serum of 32 patients with nephroblastoma and 12 controls with quantitative real‐time PCR. Three miRNAs were further tested in an independent validation set including sera of patients with renal tumors other than Wilms. Results In total, 14 miRNAs showed significantly higher abundance in serum of patients with nephroblastoma than in controls. The miRNAs with highest diagnostic potentials included miRs‐130b‐3p, ‐100‐5p, and ‐143‐3p with an AUC of 0.94, 0.90, and 0.89, respectively. A signature based on these three miRNAs to differentiated patients from controls with an accuracy of 84.58%, a sensitivity of 76.67%, and a specificity of 92.5%. Higher expression of miRs‐100‐5p and ‐130b‐3p was confirmed in an independent validation set. The signature based on miRs‐100‐5p and ‐130b‐3p differentiated patients with nephroblastoma from healthy controls with an accuracy, sensitivity, and specificity of 79.6%, 69.2%, and 90.0%, respectively. Conclusion In summary, we provide first evidence that serum miR‐100‐5p and ‐130b‐3p hold potential as biomarker for WT irrespective of the subtype and that expression level of these miRNA in serum is unaffected by differences in serum collection. Pediatr Blood Cancer 2015;62:1360–1367. © 2015 Wiley Periodicals, Inc.